Efektivitas Penerapan E-Commerce Dalam Perkembangan Usaha Mikro Kecil dan Menengah di Kota Medan - Sudarsono Sudarsono; Adhi Surya Harahap (Pajak dan Manajemen Keuangan, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important and strategic role in national economic development. Apart from playing a role in economic growth and employment, the problem formulation in this research also plays a role in providing development results. What factors influence the effectiveness of E-commerce on the development of MSMEs in Medan City. The type of data used is qualitative research, namely data that aims to gain a deeper understanding, develop theories and describe reality. The data is in the form of numbers which include a general description of the business and organizational structure. Process approach in running e-commerce with complete information. The E-commerce Target Approach has been able to show that there are targets to be achieved with its implementation.